2014
DOI: 10.1093/ntr/ntu057
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “Active Ingredients” of an Online Smoking Intervention: A Randomized Factorial Trial

Abstract: introduction: Research needs to systematically identify which components increase online intervention effectiveness (i.e., active ingredients). This study explores the effects of 4 potentially important design features in an Internet-based, populationlevel smoking intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 48 publications
(53 reference statements)
3
35
0
Order By: Relevance
“…As in our prior research with smokers who are not yet ready to quit [10-12], both phase 1 and phase 2 participants were interested in getting assistance in changing their smoking behavior, even though they were not ready to commit to quitting. Notably, 88% of phase 2 survey respondents expressed interest in an app to help them reduce their smoking and 91% expressed interest in an app to help them decide “if, when, or how” to quit, with nearly half of participants saying that learning how to quit was “very appealing.” This suggests that mHealth tools targeting this population should have a broader focus than cessation, even though the content should still help users understand the process of quitting for when they are ready.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our prior research with smokers who are not yet ready to quit [10-12], both phase 1 and phase 2 participants were interested in getting assistance in changing their smoking behavior, even though they were not ready to commit to quitting. Notably, 88% of phase 2 survey respondents expressed interest in an app to help them reduce their smoking and 91% expressed interest in an app to help them decide “if, when, or how” to quit, with nearly half of participants saying that learning how to quit was “very appealing.” This suggests that mHealth tools targeting this population should have a broader focus than cessation, even though the content should still help users understand the process of quitting for when they are ready.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, we found precontemplative and contemplative smokers were receptive to both counseling [10,11] and Internet-based programs [12] when these programs were designed to help them make informed decisions about their smoking behavior (as opposed to quitting, per se), and as a consequence, many ultimately quit smoking. Thus, we hypothesized that smokers who are not yet ready to quit could also be interested in using mHealth apps, if these programs are designed to address their needs and interests and marketed or distributed in a way to encourage their use when people are not actively seeking treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to address self-selected treatment adherence through approaches such as modified intent-to treat analyses (19) in which only participants exposed to the intervention are included in outcome analyses (20, 21). Although this approach allows for a meaningful comparison between participants exposed and not exposed to an intervention, risks of this approach are that it can elevate rates of false positive findings due to the use of post-randomization exclusion criteria, fail to account for differential engagement by study arm, reduce the generalizability of conclusions, and increase study costs by requiring larger sample sizes.…”
mentioning
confidence: 99%
“…Our study builds on work by Strecher (23), McClure (20, 24), and others (25, 26) that has focused on the role of engagement in promoting abstinence. The first strategy in this trial was a theory-driven social network (SN) approach to increase the proportion of individuals that participate in an existing online social network for cessation.…”
mentioning
confidence: 99%
“…Thus, associations between component use and outcomes would be highly confounded by self-selection. Factorial experiments that randomize individuals to mHealth components would be better suited to answering questions about what components produce treatment efficacy (Collins, Dziak, Kugler, & Trail, 2014; McClure et al, 2014). …”
Section: Discussionmentioning
confidence: 99%